Method for producing carbon coated graphite material
By crushing, graphitizing, crushing, adhesion and firing the mesophase microsphere graphite particles, carbonaceous coated graphite material was prepared, which solved the problem of difficulty in taking into account both the discharge capacity and the fast charging and discharge characteristics in the prior art, and achieved high electrode density, excellent charge and discharge efficiency and fast charging and discharge characteristics.
Patent Information
- Application Number
- CN202280002280.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-01
- Filing Date
- 2022-02-04
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-02-04
AI Technical Summary
The discharge capacity and fast charging and discharge characteristics of mesophase microsphere graphite particles are difficult to take into account in the prior art, and when increasing the electrode density, the particle orientation is not easy to be parallel to the current collector, affecting the cycle characteristics.
After pulverizing the intermediate phase microspheres, graphitization is carried out in the presence of silicon and iron, and then crushing and adhering the carbonaceous precursor. Finally, the carbonaceous precursor becomes carbonaceous and coats the graphite material, thereby improving the electrode density and discharge capacity, and optimizing the charge and discharge characteristics.
As the negative electrode material for lithium ion secondary batteries, high electrode density, high discharge capacity, excellent initial charge and discharge efficiency and excellent fast charge and discharge characteristics are achieved, especially excellent initial charge and discharge efficiency and fast charge and discharge characteristics.
Smart Images

Figure BDA0003757714470000131 
Figure HDA0003757714480000011
Abstract
Description
Technical Field
[0001] The invention relates to a method for producing a carbonaceous coated graphite material. Background Art
[0002] Compared with other secondary batteries, lithium-ion secondary batteries have excellent characteristics of high voltage and high energy density, so they are widely used as power sources for battery equipment. In recent years, lithium-ion secondary batteries have gradually been used for automotive applications, and fast charge and discharge characteristics and cycle characteristics have become more important than ever before.
[0003] The negative electrode material of the above-mentioned lithium ion secondary battery usually uses carbon material. Among them, graphite is widely used because of its excellent charge and discharge characteristics, showing high discharge capacity and potential flatness. Graphite that can be used as a negative electrode material, graphite particles of natural graphite, artificial graphite, etc., mesophase asphalt and mesophase microspheres heat-treated with tar and asphalt as raw materials, and the whole mesophase graphite particles or mesophase microsphere graphite particles obtained by heat-treating the mesophase asphalt and mesophase microspheres, making the particulate or fibrous mesophase asphalt oxidized and infusible, and the mesophase graphite particles or mesophase graphite fibers obtained by heat-treating, and the composite graphite particles obtained by heat-treating natural graphite or artificial graphite with tar, asphalt, etc., etc.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2007-31233
[0007] Patent Document 2: Japanese Patent Application Laid-Open No. 4-237971
[0008] Patent Document 3: Japanese Patent Application Publication No. 2007-191369 Summary of the invention
[0009] Problems to be solved by the invention
[0010] In the above-mentioned graphite material, especially the mesophase microsphere graphite particles, because the crystal structure in the particle develops in a random direction, therefore, it is not easy to be oriented parallel to the collector when the electrode density is increased, and has the characteristics of excellent cycle characteristics. On the other hand, compared with natural graphite, the crystallinity is lower and the discharge capacity is smaller. In addition, the shape of the mesophase microsphere graphite particles is spherical, therefore, there is a lack of contacts between particles, and there is a tendency of poor rapid charge and discharge characteristics.
[0011] Therefore, attempts have been made to improve the discharge capacity and rapid charge and discharge characteristics of mesophase microspherical graphite particles.
[0012] Regarding discharge capacity, it is known that a method of increasing the degree of graphitization by adding metals or metal compounds such as iron, aluminum, nickel, cobalt, and silicon as graphitization catalysts is used. For example, Patent Document 1 discloses a technique for particularly increasing discharge capacity by using iron and silicon elements as graphitization catalysts at a specific ratio. However, the effect on rapid charge and discharge characteristics is unclear.
[0013] In addition, as a technology for improving rapid charge and discharge characteristics, there is a known method of using a conductive material such as vapor-grown carbon fiber in combination or composite with a graphite material (Patent Document 2). However, since the discharge capacity and initial charge and discharge efficiency of the conductive material itself are lower than those of the graphite material, these characteristics decrease with the amount added. That is, it is difficult to take both discharge capacity and rapid charge and discharge characteristics into account in the prior art.
[0014] In addition, Patent Document 3 discloses a method for obtaining microscopic graphite particles with excellent rapid charge and discharge characteristics by mechanically removing microscopic protrusions produced by graphitization and further separating them. However, when such microparticles are pressed into an electrode, the density is difficult to increase, and there is a problem that the energy density cannot be increased. In addition, in this method, the yield of the separation process is extremely low and cannot be practically applied in industry.
[0015] In recent years, negative electrode materials for lithium ion secondary batteries are sometimes required to be excellent in both initial charge and discharge efficiency and rapid charge and discharge efficiency.
[0016] The present invention has been completed in view of the above-mentioned situation, and its purpose is to provide a method for manufacturing a graphite material which can be used as a negative electrode material for lithium-ion secondary batteries, which can obtain high electrode density, high discharge capacity, excellent initial charge and discharge efficiency and excellent rapid charge and discharge characteristics (rapid charge rate and rapid discharge rate), especially excellent initial charge and discharge efficiency and rapid charge and discharge characteristics, and is simple and inexpensive in industry.
[0017] Methods for solving problems
[0018] The present invention provides the following [1] to [7].
[0019] [1] A method for producing a carbonaceous coated graphite material, the method comprising:
[0020] A crushing step of crushing the fired product of the intermediate phase microspheres; a graphitization step of graphitizing the crushed product obtained in the above crushing step in the presence of silicon and iron elements; a crushing step of crushing the graphitized product obtained in the above graphitization step; an attachment step of attaching a carbonaceous precursor to the crushed product obtained in the above crushing step; and a coating step of calcining the crushed product to which the above carbonaceous precursor is attached so that the above carbonaceous precursor becomes carbonaceous, and coating the above crushed product with the above carbonaceous.
[0021] [2] The method for producing a carbonaceous coated graphite material according to [1] above, wherein the average particle size of the pulverized product is 10.0 μm or more and 20.0 μm or less.
[0022] [3] A method for producing a carbonaceous coated graphite material according to [1] or [2] above, wherein the amount of the silicon element added is greater than 1 part by mass and less than 5 parts by mass relative to 100 parts by mass of the pulverized material, and the amount of the iron element added is greater than 1 part by mass and less than 5 parts by mass relative to 100 parts by mass of the pulverized material.
[0023] [4] The method for producing a carbonaceous coated graphite material according to any one of [1] to [3] above, wherein the crushing step includes a mechanochemical treatment.
[0024] [5] The method for producing a carbonaceous coated graphite material according to any one of [1] to [4] above, wherein the coating amount of the carbonaceous material is 0.5 to 15.0% by mass.
[0025] [6] The method for producing a carbonaceous coated graphite material according to any one of [1] to [5], wherein the average particle size of the graphite material is 10.0 μm or more and 20.0 μm or less, and d 002 The specific surface area measured by the BET method is 2.0 m 2 / g or more, and the volume of micropores smaller than 0.1 μm measured by mercury intrusion porosimetry is 10.0 μL / g or more.
[0026] [7] The method for producing a carbonaceous coated graphite material according to any one of [1] to [6] above, wherein the graphite material is a negative electrode material for a lithium ion secondary battery.
[0027] Effects of the Invention
[0028] According to the manufacturing method of the present invention, it is possible to obtain industrially simply and inexpensively as a negative electrode material for lithium-ion secondary batteries, which exhibits high electrode density, high discharge capacity, excellent initial charge and discharge efficiency and excellent rapid charge and discharge characteristics, especially a graphite material with excellent initial charge and discharge efficiency and rapid charge and discharge characteristics, and can meet the rapid charge and discharge characteristics required for secondary batteries in recent years. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a cross-sectional view schematically showing the structure of a button-type evaluation battery used in a charge and discharge test in Examples.
[0030] Explanation of symbols
[0031] 1 Exterior cover
[0032] 2 Negative electrode mixture
[0033] 3 Outer cans
[0034] 4 pairs of electrodes (positive electrode)
[0035] 5. Partition
[0036] 6 Insulation pad
[0037] 7a, 7b Current collector DETAILED DESCRIPTION
[0038] Hereinafter, the present invention will be described in detail.
[0039] (Mesophase Microspheres)
[0040] The mesophase microspheres serving as the starting material of the present invention can be obtained by heat treating a petroleum-based or coal-based asphalt containing, for example, 0.01 to 2 mass %, preferably 0.3 to 0.9 mass % of free carbon at, for example, 350 to 1000°C, preferably 400 to 600°C, and more preferably 400 to 450°C.
[0041] Examples of the asphalts include coal tar, tar light oil, tar medium oil, tar heavy oil, naphthalene oil, anthracene oil, coal tar pitch, asphalt oil, oxygen-crosslinked petroleum asphalt, heavy oil, and the like, and coal tar pitch is preferred.
[0042] The average particle size of the mesophase microspheres is, for example, 20 to 70 μm, preferably 30 to 50 μm. When the particle size is less than 20 μm, the effect of improving the discharge capacity may be insufficient.
[0043] (Firing)
[0044] The mesophase microspheres are fired, for example, at 400 to 800° C. for 1 to 6 hours in an inert gas atmosphere to prepare mesophase microsphere fired products. By preparing mesophase microsphere fired products, fusion during graphitization can be prevented.
[0045] (crushed)
[0046] In the step of pulverizing the calcined mesophase microspheres of the present invention, the pulverization method is not particularly limited, and any of a dry method and a wet method can be used, preferably a dry method. The average particle size after pulverization is preferably 10.0 to 20.0 μm, more preferably 10.0 to 17.5 μm, further preferably 10.0 to 16.0 μm, and particularly preferably 10.0 to 15.0 μm. In addition, classification may be performed to adjust the average particle size.
[0047] (Silicon and Iron)
[0048] The silicon element and the iron element of the present invention include not only these elemental simple substances, but also silicon compounds and iron compounds. In addition, as long as they are evaporated in the graphitization step described later, other metal elements may be included, and they may also be in the form of alloys. Silicon oxide, silicon carbide, iron oxide, iron hydroxide, and ferrosilicon are preferred.
[0049] The silicon element and the iron element are preferably in powder form, and the average particle size thereof is preferably 5 μm or less, and more preferably 1 μm or less.
[0050] The addition amount of silicon element and iron element is preferably 1 to 5 parts by mass, respectively, in terms of element monomers, relative to 100 parts by mass of the pulverized product of the sintered product of the mesophase microspheres. When it is less than 1 part by mass, the effect of the present invention may not be fully obtained. When it exceeds 5 parts by mass, the graphite material may melt and adhere in the graphitization process, and the battery characteristics may be reduced.
[0051] Silicon and iron are preferably uniformly mixed with the pulverized material of the mesophase microsphere sintered material before graphitization. The mixing method is not particularly limited, and a known mixer such as a stirring method, a rotating method, a wind method, etc. can be used. In addition, the mesophase microsphere sintered material, silicon and iron can be mixed in advance before the pulverization step, and the pulverization and mixing can be performed simultaneously.
[0052] (Graphitization)
[0053] The graphitization in the present invention can be carried out by, for example, a method of heat treatment using a well-known high-temperature furnace such as an Acheson furnace. As a result, silicon and iron elements will decompose / evaporate, and therefore substantially do not remain in the obtained graphite material. Of course, the heat treatment temperature is above the temperature at which silicon and iron elements evaporate, specifically, for example, above 2500°C, preferably above 2800°C, more preferably above 3000°C, and further preferably above 3100°C. The upper limit is 3300°C. Graphitization is preferably carried out in a non-oxidizing gas atmosphere. The time required for graphitization cannot be generalized, for example, it is about 1 to 20 hours.
[0054] It should be noted that whether silicon or iron remains after graphitization can be confirmed by ordinary combustion analysis, and is preferably less than 0.03 mass % and more preferably less than 0.01 mass % in terms of ash content.
[0055] (broken)
[0056] The present invention includes a process of crushing the graphite. The reason is that in the graphitization process, silicon reacts with carbon materials and graphite particles fuse to each other, so they need to be separated into primary particles again. The average particle size after crushing is preferably in the range of 0.9 to 1.0 compared with the average particle size before graphitization. When the ratio of the average particle size is less than 0.9, it becomes excessively crushed, and sometimes the initial charge and discharge efficiency is reduced. When the ratio of the average particle size exceeds 1.0, the crushing becomes insufficient, and sometimes the electrode density is reduced.
[0057] The crushing method is not particularly limited as long as the above average particle size can be achieved, and a known crusher such as a hammer mill, a stirred mill, a jet mill, a ball mill, a bead mill, etc. can be used. Preferably, a method using a mechanochemical treatment machine (shear compression treatment machine) such as a HYBRIDIZATION system (Hybridization system) (Nara Machinery Manufacturing Co., Ltd.), a Mechanofusion system (Hosokawa Micron Co., Ltd.), Nobilta (Hosokawa Micron Co., Ltd.), a dry mill (Dry-Attritor) (NIPPON COKE & ENGINEERING Co., Ltd.) is mentioned.
[0058] The reason why the method using a mechanochemical treatment machine is preferred is that the edge faces of graphite exposed by the crushing are low-crystallized due to friction, and higher initial charge and discharge efficiency can be obtained.
[0059] (Attachment)
[0060] In the present invention, a carbonaceous precursor is attached to the crushed product (crushed graphitized product) obtained in the crushing step. The attachment method is not particularly limited, and for example, a solid, liquid, molten, or solution carbonaceous precursor may be used and mixed with the crushed product, impregnated with the crushed product, or sprayed on the crushed product.
[0061] The gas atmosphere during the above treatment is not particularly limited, and may be, for example, an air atmosphere.
[0062] The temperature during the treatment is preferably 5° C. or higher, more preferably 10° C. or higher, and further preferably 25° C. or higher. On the other hand, the temperature is preferably 150° C. or lower, more preferably 100° C. or lower, and further preferably 60° C. or lower.
[0063] (Carbonaceous Precursor)
[0064] Examples of the carbonaceous precursor include tar pitches and / or resins, which are carbon materials having lower crystallinity than graphite and which do not turn into graphite crystals even when subjected to a high-temperature treatment required for graphitization.
[0065] Examples of the tar pitches include coal tar, tar light oil, tar medium oil, tar heavy oil, naphthalene oil, anthracene oil, coal tar pitch, asphalt oil, mesophase pitch, oxygen-crosslinked petroleum pitch, and heavy oil.
[0066] Examples of the resins include thermoplastic resins such as polyvinyl alcohol and polyacrylic acid; thermosetting resins such as phenol resin and furan resin; and the like.
[0067] From the viewpoint of cost, the carbonaceous precursor preferably does not contain resins and is formed only of tar pitches. As such a carbonaceous precursor, for example, a carbonaceous precursor containing 80% by mass or more of coal tar pitch is suitable.
[0068] (Firing)
[0069] In the present invention, the crushed product to which the carbonaceous precursor is attached obtained in the attachment step is fired to convert the carbonaceous precursor into carbon, thereby obtaining a carbonaceous coated graphite material.
[0070] The firing method is not particularly limited, but firing is preferably performed in an inert gas atmosphere to prevent oxidation during firing. In this case, a tubular furnace is preferably used.
[0071] Regarding the gas atmosphere during firing, examples of the non-oxidizing gas atmosphere include an argon atmosphere, a helium atmosphere, and a nitrogen atmosphere.
[0072] The temperature during calcination (calcination temperature) is preferably 700° C. or higher, more preferably 900° C. or higher. On the other hand, the calcination temperature is preferably 2000° C. or lower, more preferably 1300° C. or lower, and further preferably 1200° C. or lower.
[0073] Specifically, for example, sintering is preferably performed at 700° C. or higher and 2000° C. or lower in a nitrogen flow.
[0074] The calcination time is preferably 5 minutes or longer. On the other hand, the calcination time is preferably 30 hours or shorter.
[0075] As a method of raising the temperature to the calcining temperature, various methods such as linear temperature increase and stepwise temperature increase in which the temperature is maintained at a certain interval can be adopted.
[0076] (Carbon coated graphite material)
[0077] The carbonaceous coated graphite material obtained by the production method of the present invention (hereinafter referred to as the carbonaceous coated graphite material of the present invention) is highly crystalline and exhibits optical anisotropy. The crystallinity of graphite can be measured by the average interplanar spacing d of the (002) plane in wide-angle X-ray diffraction. 002 As an indicator, the d of the carbonaceous coated graphite material of the present invention is 002 It is preferably 0.3360 nm or less, and more preferably 0.3358 nm or less.002 When the diameter exceeds 0.3360 nm, a high discharge capacity may not be obtained.
[0078] Here, the average interplanar spacing d of the (002) plane in wide-angle X-ray diffraction is 002 The calculation is performed based on the position of the diffraction peak of the (002) plane of the carbonaceous coated graphite material using CuKα rays as X-rays and high-purity silicon as a standard substance. The calculation method is based on the Gakushin method (a measurement method established by the 17th Committee for the Promotion of Science in Japan), specifically, the value measured by the method described in "Carbon Fiber" [Otani Sugiro, pp. 733-742 (March 1986), Kindai Editing Co., Ltd.].
[0079] In addition, the carbonaceous coated graphite material of the present invention is porous and exhibits excellent initial charge and discharge efficiency and excellent rapid charge and discharge characteristics as a negative electrode material for lithium ion secondary batteries. The specific surface area of the carbonaceous coated graphite material of the present invention measured by the BET method is preferably 2.0 m 2 / g or more, more preferably 2.1m 2 / g or more, more preferably 2.2m 2 / g or more, particularly preferably 2.5m 2 / g or more. The upper limit is preferably 5.0 m 2 / g.
[0080] In addition, the volume of micropores smaller than 0.1 μm measured by mercury intrusion porosimetry is preferably 10.0 μL / g or more, more preferably 10.2 μL / g or more. The upper limit is preferably 20.0 μL / g. 2 / g, or when the volume of micropores smaller than 0.1 μm is smaller than 10.0 μL / g, the rapid charge and discharge characteristics may be deteriorated.
[0081] The average particle size of the carbonaceous coated graphite material of the present invention is preferably 10.0 to 20.0 μm, more preferably 10.0 to 17.5 μm, further preferably 10.0 to 16.0 μm, and particularly preferably 10.0 to 15.0 μm.
[0082] (Carbon coating amount)
[0083] The carbonaceous coating amount in the carbonaceous coated graphite material of the present invention is preferably 0.5% by mass or more, more preferably 0.7% by mass or more, and even more preferably 1.0% by mass or more.
[0084] When the carbonaceous coating amount is within this range, the active edge surfaces of the crushed objects are easily coated, and the initial charge and discharge efficiency is more excellent.
[0085] On the other hand, the carbonaceous coating amount in the carbonaceous coated graphite material of the present invention is preferably 15.0% by mass or less, more preferably 12.0% by mass or less, and even more preferably 10.0% by mass or less.
[0086] When the coating amount of the carbonaceous material is within this range, the amount of carbonaceous material having a low discharge capacity is relatively reduced, and the discharge capacity is more excellent.
[0087] In addition, when the coating amount of the carbonaceous material is within this range, the amount of the carbonaceous material precursor used is reduced, so that fusion is less likely to occur during adhesion and firing, and the cracking and peeling of the finally obtained carbonaceous material are suppressed, resulting in a more excellent initial charge and discharge efficiency.
[0088] The carbonaceous coating amount may be within the above range as long as the average value of the entire carbonaceous coated graphite material is within the above range. All carbonaceous coated graphite materials do not need to be within the above range, and a part of them may include carbonaceous coated graphite materials outside the above range.
[0089] The carbonaceous coating amount was determined from the residual carbon amount by firing only the carbonaceous precursor under the same conditions as those for firing the crushed product to which the carbonaceous precursor was attached.
[0090] (Lithium-ion secondary battery)
[0091] The carbonaceous coated graphite material of the present invention can be used as a negative electrode material of a lithium ion secondary battery. There is no particular limitation on the components of the battery other than the negative electrode material, namely the positive electrode material, electrolyte, separator, binder, collector, etc., and known techniques related to lithium ion secondary batteries can be applied.
[0092] Example
[0093] Next, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. Figure 1 As shown, a button-type secondary battery for single-pole evaluation was prepared and evaluated, and the button-type secondary battery for single-pole evaluation was composed of a collector (negative electrode) 7b having a negative electrode mixture 2 having the negative electrode material of the present invention attached to at least a portion of the surface, and a counter electrode (positive electrode) 4 formed of lithium foil. The actual battery can be prepared based on the concept of the present invention and according to a known method.
[0094] In addition, in the following examples and comparative examples, the physical properties of the materials were measured by the following methods.
[0095] The average particle size is a particle size at which the cumulative frequency of the particle size distribution measured by laser diffraction particle size distribution diameter is 50% in terms of volume percentage.
[0096] The specific surface area was determined by the BET method based on nitrogen adsorption.
[0097] Average interplanar spacing d of (002) planes in wide-angle X-ray diffraction 002 It is obtained by the above-mentioned Xuezhen method.
[0098] The volume of pores with a diameter of 0.1 μm or less is determined by mercury porosimetry.
[0099] (Example 1)
[0100] [Manufacturing of carbon coated graphite materials]
[0101] Coal tar pitch was heat treated at 450°C in a nitrogen atmosphere to generate mesophase microspheres (average particle size 40 μm). Then, the asphalt matrix was extracted from the coal tar pitch using tar oil, and the mesophase microspheres were further separated from the tar oil and dried. The dried mesophase microspheres were heat treated at 500°C for 3 hours in a nitrogen atmosphere to obtain a calcined mesophase microsphere (average particle size 34 μm).
[0102] Next, the calcined mesophase microspheres were crushed with a hammer mill to an average particle size of 15 μm. 100 parts by mass of the obtained crushed material, 4.3 parts by mass of silicon dioxide (2 parts by mass of silicon element) and 2.9 parts by mass of iron oxide (2 parts by mass of iron element) were put into a screw mixer and mixed for 30 minutes. The obtained mixture was filled into a graphite crucible and graphitized by heat treatment at 3150°C for 5 hours in an Acheson electric furnace. The ash content (combustion method) of the obtained graphitized material was less than 0.01%.
[0103] Then, the obtained graphite was put into a Mechanofusion system (Hosokawa Micron Co., Ltd.) and operated at a rotor peripheral speed of 20 m / s for 30 minutes to perform crushing (mechanical chemical treatment).
[0104] Coal tar pitch as a carbonaceous precursor was added to the sieved crushed product, heated to 50°C and mixed for 30 minutes using a biaxial kneader. The carbonaceous precursor was added in an amount such that the final carbonaceous obtained became the content shown in Table 1 below. Then, a tubular furnace was used to calcine at 1100°C for 10 hours under a 5L / min nitrogen flow (in a non-oxidizing gas atmosphere). Finally, the calcined product was passed through a 53μm sieve to obtain a carbonaceous coated graphite material in which the crushed product (mesophase microsphere graphitized product) was coated with carbonaceous.
[0105] The physical properties (average particle size, specific surface area, etc.) of the obtained carbonaceous coated graphite material were determined by the above method. The results are shown in Table 1 below.
[0106] [Preparation of negative electrode mixture paste]
[0107] Next, the obtained carbonaceous coated graphite material was used as the negative electrode material to prepare the negative electrode. First, 96 parts by mass of the negative electrode material, 2 parts by mass of carboxymethyl cellulose as a binder, and 2 parts by mass of styrene-butadiene rubber were added to water and stirred to prepare a negative electrode mixture paste. Then, the negative electrode mixture layer coated on the copper foil was pressed at a pressure of 150 MPa. Furthermore, the copper foil and the negative electrode mixture layer were punched into a cylindrical shape with a diameter of 15.5 mm, and a working electrode (negative electrode) having a negative electrode mixture layer closely attached to the copper foil was prepared.
[0108] [Fabrication of counter electrode (positive electrode)]
[0109] Next, a button-type secondary battery for single-pole evaluation was fabricated using the produced negative electrode. As the positive electrode, a current collector formed of a nickel mesh and an electrode plate formed of a lithium metal foil closely attached to the current collector were used.
[0110] [Electrolyte / Separator]
[0111] As for the electrolyte, LiPF6 was dissolved in a mixed solvent of 33 volume % of ethylene carbonate and 67 volume % of ethyl methyl carbonate at a concentration of 1 mol / L to prepare a non-aqueous electrolyte. The obtained non-aqueous electrolyte was impregnated into a polypropylene porous body having a thickness of 20 μm to prepare a separator impregnated with the electrolyte.
[0112] [Evaluation of battery structure]
[0113] Figure 1 A structure of a button-type secondary battery is shown as an evaluation battery.
[0114] The insulating pad 6 is sandwiched between the edges of the outer cover 1 and the outer can 3, and the two edges are riveted to seal. Inside the outer can 3, a current collector 7a formed of a nickel mesh, a cylindrical counter electrode (positive electrode) 4 formed of a lithium foil, a separator 5 impregnated with an electrolyte, and a current collector (negative electrode) 7b formed of a copper foil with a negative electrode mixture 2 attached thereto are sequentially stacked to form a battery system.
[0115] The above-mentioned evaluation battery is manufactured in the following manner: a separator 5 impregnated with an electrolyte is sandwiched between a working electrode (negative electrode) formed by a collector 7b and a negative electrode mixture 2, and a counter electrode 4 tightly attached to the collector 7a, and then the collector 7b is accommodated in an outer cover 1, the counter electrode 4 is accommodated in an outer can 3, the outer cover 1 and the outer can 3 are joined, and an insulating gasket 6 is further inserted into the edge of the outer cover 1 and the outer can 3, and the two edge portions are riveted to seal.
[0116] The evaluation battery produced in the above manner was subjected to the following charge and discharge test at 25° C., and the discharge capacity, initial charge and discharge efficiency, rapid charge rate, and rapid discharge rate were calculated.
[0117] In addition, the electrode density was calculated from the thickness and the mass of the negative electrode mixture.
[0118] [Discharge capacity and initial charge and discharge efficiency]
[0119] After charging at a constant current of 0.9 mA until the circuit voltage reaches 0 mV, switch to constant voltage charging at the moment when the circuit voltage reaches 0 mV, and continue charging until the current value is 20 μA. The charge capacity per unit mass (unit: mAh / g) is calculated based on the amount of power supplied during this period. Then, stop for 120 minutes. Next, discharge at a constant current value of 0.9 mA until the circuit voltage reaches 1.5 V, and the discharge capacity per unit mass (unit: mAh / g) is calculated based on the amount of power supplied during this period. The initial charge and discharge efficiency is calculated using formula (1).
[0120] Initial charge and discharge efficiency (%) = (discharge capacity / charge capacity) × 100 (1)
[0121] In addition, in this test, the process of absorbing lithium ions in the negative electrode material is referred to as charging, and the process of desorbing lithium ions from the negative electrode material is referred to as discharging.
[0122] The discharge capacity is preferably 357 mAh / g or more, more preferably 357 to 365 mAh / g. The initial charge and discharge efficiency is preferably 92% or more, more preferably 92 to 95%.
[0123] [Fast charging rate]
[0124] Next, in the second cycle, fast charging is performed.
[0125] The current value is set to 6 mA, and constant current charging is performed until the circuit voltage reaches 0 mV. The charging capacity is calculated and the fast charging rate is calculated using formula (2).
[0126] Rapid charge rate (%) = (rapid constant current charge capacity / initial discharge capacity) × 100···(2)
[0127] The rapid charging rate is preferably 40% or more, more preferably 40 to 55%, and even more preferably 43 to 55%.
[0128] [Fast discharge rate]
[0129] In the same second cycle, rapid discharge was performed.
[0130] After switching to constant voltage charging and fully charging in the same manner as in the first cycle, constant current discharge was performed at a current value of 12 mA until the circuit voltage reached 1.5 V. The rapid discharge rate was calculated from the obtained discharge capacity using equation (3).
[0131] Rapid discharge rate (%) = (rapid discharge capacity / initial discharge capacity) × 100 (3)
[0132] The rapid discharge rate is preferably 92% or more, more preferably 92 to 98%.
[0133] (Example 2)
[0134] In Example 1, 2.1 parts by mass of silicon dioxide (1 part by mass of silicon element) and 4.3 parts by mass of iron oxide (3 parts by mass of iron element) were mixed with the pulverized material of the calcined mesophase microspheres. Graphite material preparation and battery characteristics evaluation were performed in the same manner as in Example 1 except for the above.
[0135] (Example 3)
[0136] In Example 1, 6.4 parts by mass of silicon dioxide (3 parts by mass of silicon element) and 1.4 parts by mass of iron oxide (1 part by mass of iron element) were mixed with the pulverized material of the calcined mesophase microspheres. Graphite material preparation and battery characteristics evaluation were performed in the same manner as in Example 1 except for the above.
[0137] (Example 4)
[0138] In Example 1, the carbonaceous precursor was added in such an amount that the carbonaceous material finally obtained had a content shown in the following Table 1. Production of a graphite material and evaluation of battery characteristics were carried out in the same manner as in Example 1 except for the above.
[0139] (Comparative Example 1)
[0140] In Example 1, the step of attaching a carbonaceous precursor to the crushed material and then firing the crushed material was not performed.
[0141] That is, in the same manner as in Example 1, the physical properties and battery characteristics of the graphite after the mechanochemical treatment were evaluated.
[0142] (Comparative Example 2)
[0143] In Comparative Example 1, 2.1 parts by mass of silicon dioxide (1 part by mass of silicon element) and 1.4 parts by mass of iron oxide (1 part by mass of iron element) were mixed with the pulverized material of the calcined mesophase microspheres. Graphite material preparation and battery characteristics evaluation were performed in the same manner as in Comparative Example 1 except for the above.
[0144] (Comparative Example 3)
[0145] In Comparative Example 1, 2.1 parts by mass of silicon dioxide (1 part by mass of silicon element) and 4.3 parts by mass of iron oxide (3 parts by mass of iron element) were mixed with the pulverized material of the calcined mesophase microspheres. Graphite material preparation and battery characteristics evaluation were performed in the same manner as in Comparative Example 1 except for the above.
[0146] (Comparative Example 4)
[0147] In Comparative Example 1, 6.4 parts by mass of silicon dioxide (3 parts by mass of silicon element) and 1.4 parts by mass of iron oxide (1 part by mass of iron element) were mixed with the pulverized material of the calcined mesophase microspheres. Graphite material preparation and battery characteristics evaluation were performed in the same manner as in Comparative Example 1 except for the above.
[0148] (Comparative Example 5)
[0149] In Example 1, graphitization was performed without adding silicon dioxide and iron oxide. Production of a graphite material and evaluation of battery characteristics were performed in the same manner as in Example 1 except for the above.
[0150] (Comparative Example 6)
[0151] In Example 1, the obtained graphite was not crushed. Production of a graphite material and evaluation of battery characteristics were carried out in the same manner as in Example 1 except for the above.
[0152] The above evaluation results are shown in Table 1 below.
[0153]
[0154] As shown in Table 1, the carbonaceous coated graphite material of the present invention exhibits high electrode density, high discharge capacity, excellent initial charge and discharge efficiency, and excellent rapid charge and discharge characteristics as a negative electrode material for lithium ion secondary batteries. In particular, both the initial charge and discharge efficiency and the rapid charge and discharge characteristics are excellent, achieving a balance between the two.
[0155] The carbonaceous coated graphite material of the present invention has excellent rapid charge and discharge efficiency although its micropore volume is smaller than that of the comparative example. It can be speculated that this is because the amorphous carbon in the film (carbonaceous) has a structure suitable for accepting lithium by coating the carbonaceous material after mechanochemical treatment.
Claims
1. A method for producing a carbonaceous coated graphite material, the method comprising: A pulverizing step of pulverizing the calcined product of the mesophase microspheres; A graphitization step of graphitizing the pulverized product obtained in the pulverization step in the presence of silicon and iron elements; A crushing step of crushing the graphite obtained in the graphitization step; a step of attaching a carbonaceous precursor to the crushed product obtained in the crushing step; as well as a coating step of calcining the crushed product to which the carbonaceous precursor is attached so as to convert the carbonaceous precursor into carbonaceous material, and coating the crushed product with the carbonaceous material; The micropore volume of the carbonaceous coated graphite material smaller than 0.1 μm measured by mercury intrusion porosimetry is greater than 10.0 μL / g.
2. The method for producing a carbonaceous coated graphite material according to claim 1, wherein: The average particle size of the pulverized product is 10.0 μm or more and 20.0 μm or less.
3. The method for producing a carbonaceous coated graphite material according to claim 1 or 2, wherein: The amount of the silicon element added is 1 part by mass or more and 5 parts by mass or less relative to 100 parts by mass of the pulverized product. The amount of the iron element added is 1 part by mass or more and 5 parts by mass or less relative to 100 parts by mass of the pulverized product.
4. The method for producing a carbonaceous coated graphite material according to any one of claims 1 to 3, wherein: The crushing process includes mechanochemical treatment.
5. The method for producing a carbonaceous coated graphite material according to any one of claims 1 to 4, wherein: The coating amount of the carbonaceous material is 0.5 to 15.0% by mass.
6. The method for producing a carbonaceous coated graphite material according to any one of claims 1 to 5, wherein: The average particle size of the graphite material is 10.0 μm or more and 20.0 μm or less. 002 The specific surface area measured by the BET method is 2.0 m 2 / g or above.
7. The method for producing a carbonaceous coated graphite material according to any one of claims 1 to 6, wherein: The graphite material is a negative electrode material for a lithium-ion secondary battery.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP1992237971A
Method for producing fine graphite particle
JP2007191369A
Carbonaceous coated graphite particles for negative-electrode material of lithium-ion secondary cell, negative electrode for lithium-ion secondary cell, and lithium-ion secondary cell
CN107534148A
Graphite particle, lithium ion secondary battery, negative electrode material for it, and negative electrode
JP2004134244A
Method for producing graphite material
JP2007031233A